An Examination of Preschool Teachers’ Identification of Risk Groups and The Intervention Plans They Implement - Berrin Akman; Feyza Özkan Yıldız (e-Kafkas Eğitim Araştırmaları Dergisi)
Individuals whose educational needs differ for various reasons can benefit from appropriate educational services through early assessment and diagnosis practices. At-risk children who fail to achieve adequate development in general education classes need more intensive education. For these individuals to benefit effectively from the education process, it is important to organize it according to their characteristics. Identifying the children in the risk group is possible through teachers’ experience, observation, and assessment practices. In this context, if a class includes children who are considered to be in the risk group, the educational assessment process should be initiated. The aim of this study is to examine preschool teachers’ identification of risk groups in their classes and the intervention plans they implement. Fifteen preschool teachers from the central district of Konya province of Türkiye participated in the study, which was conducted as a case study, a qualitative research method. Data were collected through interviews. The findings obtained from the data indicate that the preschool teachers participating in the study think early intervention is mostly aimed at children with special needs. However, children may be in the risk group due to familial, environmental, and individual factors, and preschool teachers mostly use observation and information obtained from the family while identifying these groups. The teachers stated that most socioeconomically disadvantaged children were present in their classrooms. The teachers stated that they do not implement a systematic planning process for the risk groups in their classes, but they make some changes in the education process according to the needs of the children.